ANALISIS DAN VISUALISASI HOST LIBURAN SINGKAT MENGGUNAKAN PENDEKATAN ANALISIS GEOSPASIAL - Irwan Setiawan (P3M Politeknik Negeri Indramayu, 2020)
The development of sharing economy that happened exponentially has changed the accommodation sector in the tourism and hospitality industry. The varied customer experience, facilities, and range of prices offered has made this business model an alternative to traditional accommodation services and is a favorite among tourists. The rapid development of information technology facilitates many online platforms that provide property rental services with the concept of sharing economy. This makes the tourism and hospitality industry rich in data. This study aims to analyze data on property rental advertisements focusing on short vacation services with a case study of Airbnb data in Singapore. The results of the study are expected to be used by new players or old players in the business as one of the considerations of situation analysis for making decisions. The analysis was carried out to obtain patterns and relationships from data related to prices, room types, and property distribution in the form of diagrams and maps. This study uses a visual data analysis approach using the Python programming language.